Augmenting regional and targeted delivery in the pulmonary acinus using magnetic particles - Ostrovski Y (Dove Medical Press, 2016)
Yan Ostrovski, Philipp Hofemeier, Josué Sznitman Department of Biomedical Engineering, Technion – Israel Institute of Technology, Haifa, Israel Background: It has been hypothesized that by coupling magnetic particles to inhaled therapeutics, the ability to target specific lung regions (eg, only acinar deposition), or even more so specific points in the lung (eg, tumor targeting), can be substantially improved. Although this method has been proven feasible in seminal in vivo studies, there is still a wide gap in our basic understanding of the transport phenomena of magnetic particles in the pulmonary acinar regions of the lungs, including particle dynamics and deposition characteristics.Methods: Here, we present computational fluid dynamics-discrete element method simulations of magnetically loaded microdroplet carriers in an anatomically inspired, space-filling, multi-generation acinar airway tree. Breathing motion is modeled by kinematic sinusoidal displacements of the acinar walls, during which droplets are inhaled and exhaled. Particle dynamics are governed by viscous drag, gravity, and Brownian motion as well as the external magnetic force. In particular, we examined the roles of droplet diameter and volume fraction of magnetic material within the droplets under two different breathing maneuvers.Results and discussion: Our results indicate that by using magnetic-loaded droplets, 100% of the particles that enter are deposited in the acinar region. This is consistent across all particle sizes investigated (ie, 0.5–3.0 µm). This is best achieved through a deep inhalation maneuver combined with a breath-hold. Particles are found to penetrate deep into the acinus and disperse well, while the required amount of magnetic material is maintained low (<2.5%). Although particles in the size range of ~90–500 nm typically show the lowest deposition fractions, our results suggest that this feature could be leveraged to augment targeted delivery. Keywords: inhalation medicine, targeted delivery, SPIONs, aerosol, CFD